Strategies used in the detection of acute/early HIV infections. The NIMH Multisite Acute HIV Infection Study: I. - Kerndt, Peter R; Dubrow, Robert; Aynalem, Getahun; Mayer, Kenneth H; Beckwith, Curt; Remien, Robert H; Truong, Hong-Ha M; Uniyal, Apurva; Chien, Michael; Brooks, Ronald A; Vigil, Ofilio R; Steward, Wayne T; et al. (AIDS and behavior, 2009)
Acute/early HIV infection plays a critical role in onward HIV transmission. Detection of HIV infections during this period provides an important early opportunity to offer interventions which may prevent further transmission. In six US cities, persons with acute/early HIV infection were identified using either HIV RNA testing of pooled sera from persons screened HIV antibody negative or through clinical referral of persons with acute or early infections. Fifty-one cases were identified and 34 (68%) were enrolled into the study; 28 (82%) were acute infections and 6 (18%) were early infections. Of those enrolled, 13 (38%) were identified through HIV pooled testing of 7,633 HIV antibody negative sera and 21 (62%) through referral. Both strategies identified cases that would have been missed under current HIV testing and counseling protocols. Efforts to identify newly infected persons should target specific populations and geographic areas based on knowledge of the local epidemiology of incident infections.
Keywords: Acute Disease; Adult; AIDS Serodiagnosis; Early Diagnosis; Female; HIV Infections; HIV Seropositivity; HIV-1; Humans; Male; National Institute of Mental Health (U.S.); Public Health; Referral and Consultation; Reverse Transcriptase Polymerase Chain Reaction; RNA, Viral; United States; Young Adult